Role of Cathelicidin (Ll-37) and Human Β-Defensin In Atopic Dermatitis And Psoriasis - Febrina Andarini; Nopriyati; Sarah Diba (RSUP Dr Moh Hoesin Palembang, 2020)
The Human epithelium, including the epidermis produces antimicrobial peptide (AMP)as part of innate immunity. Cathelicidin and human β-defensins are the most AMPfound on the skin. This antimicrobial peptide has a role in the response of the naturalimmune system by becoming the front line of the defense system against infection. Thediscussion of this literature review will focus on cathelicidin and human β-defensin-1which are the main AMPs that affect atopic dermatitis and psoriasis. Antimicrobialpeptides are excessively produced in lesional psoriatic scales or rosacea in contrast tothe atopic skin that shows lower AMP levels when compared with psoriasis. Despitethe impaired skin barrier which facilitates potentially pathogenic microbes to colonizethe epidermis, patients with psoriasis surprisingly present a low frequency of skininfections, whereas patients with atopic dermatitis are predominantly susceptible toparticular cutaneous bacterial, fungal and viral infections. One possible explanation ofthe fact is the difference in the expression of AMPs. DA patients have fewer AMPexpression characteristics, especially cathelicidins LL-37 and HBD-2. Research onantimicrobial use can help reduce pathogen colonization so that clinical improvementof AD occurs. In the case of psoriasis, AMP expression increases, especially LL-37 andHBD-2, showing synergistic antimicrobial activity that is effective in eradicatingmicrobial colonization, so there is no strong evidence to support antibiotic use intreating psoriasis or in preventing disease.